Feasibility of artificial reefs as coastal protection measures at the Danube Delta coast, Romania - Dinu, Irina; Gràcia, Vicente; García-León, Manuel; Lin-Ye, Jue; Stănică, Adrian; Sánchez-Arcilla, Agustín (Frontiers in Environmental Science, 2025)
Introduction: The Danube Delta coast is part of the Danube Delta Biosphere Reserve, thus being aimed to preserve its typical natural habitats. Over the last decades, human interventions along the Danube River, as well as coastal navigation and harbour protection works on the Romanian coast, have determined the reduction of sediment supply along the Danube Delta coast, which is nowadays affected by erosion on its widest part. Sustainable management plans for the Danube Delta coast include the use of working-with-nature solutions. In this work, the effectiveness of artificial reefs along the Danube Delta coast has been assessed, from the hydrodynamic point of view.Methods: The results of a previous wave climate study and a wave model have been used for this purpose. Simulations have been performed for different setup of artificial reefs, with different heights, and for extreme storms with various return periods, to test their effectiveness in reducing wave height and energy. Sea level rise has also been taken into account.Results: Our results show that artificial reefs are significantly effective in reducing the wave heights along the Danube Delta coast.Discussion: However, further detailed analysis concerning the impact of such a coastal protection solution is still needed, especially on the shoreline evolution and the local hydrodynamics.